Assessment on the severity of low density polyethylene (LDPE)/Ethylene hybrid explosion - H., Badli; Md Noor, Ariffin; Siti Zubaidah, Sulaiman; Susaidevas, Jlyas; Nur Atikah, Mahamad; Nazrah Asyhiqin, Mahamad Khariol Nizar (IOP Publishing Ltd, 2019)
The potential explosion for low-density polyethylene (LDPE) dust is greatly increased due to the presence of ethylene gas. Thus, this study was aimed to investigate the explosion severity of polyethylene/ethylene hybrid mixture in a 20-L spherical vessel. The explosion setup is equipped with two chemical ignitors and Kistler piezoelectric pressure sensors to ignite the hybrid mixture and to quantify the propagation of pressure wave during the explosion process respectively. The following hybrid explosion characteristics including the maximum explosion overpressure (Pmax), the maximum rate of pressure rise (dP/dT) and deflagration index (KST) were evaluated. This study concluded that the explosion severity of polyethylene/ethylene hybrid mixture steeply increases as the gas concentration and particle size increase to 15 g/m3 and 125 μm, beyond which the Pmax and dP/dT steadily decrease. The highest Pmax and dP/dt were recorded at 5.5 bar and, 50.5 bar/s with the KST value is 50 bar.m/s indicating the LDPE/ethylene hybrid dust explosion possess a weak explosion.